The analysis of technical process of terminal systems - Shramenko, N. Yu. (Science and Transport Progress, 2011)
The analysis of technological processes of the terminal systems is conducted, features are exposed and the basic problems of modern technology are certain. Directions of improvement technology of functioning of the terminal systems are offered.